Multibody approach in suspension system optimization - Korta, Jakub; Martowicz, Adam; Gallina, Alberto; Uhl, Tadeusz (Computer Assisted Methods in Engineering and Science, 2017)
In this paper an approach of optimization of suspension system parameters is described. Taking into consideration the stiffness and damping coefficients of springs and shock absorbers of a heavy road transport vehicle semitrailer, process of adjusting those values has been undertaken by means of the response surface methodology and a desirability function application, supported by the sensitivity computations. Two different methods of constructing metamodels: Kriging and polynomial regression have been tested and compared with a set of results obtained from the numerical multibody dynamic analysis. The objective of the undertaken efforts was to minimize the loads in the crucial points of the structure, identified as the high-risk failure areas. A number of simulations have been carried out under the set of different load cases, specially established to represent a wide range of operating conditions possible to be met during the vehicle life cycle.